Perkembangan Jiwa Agama pada Masa Al-Murahiqah (Remaja) - Muhammad Ichsan Thaib (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
This paper restricts the study in adolescence only, particularly with regard to the development of religion in their life. Many mental shocks happen in teenagers. They sometimes follow and do whatever they like which may contradict with the values in the community and even contradict with religious values. Adolescent is defined as a transition stage of development which brings individuals from childhood to adulthood. Adolescent ages are between 13 to 21 years. As for the religious mental development of teenagers, the ages range from 13 to 24 years. There are two factors that influence this development, namely: heredity factors (inheritance) and environmental factors. The development of religion in ones' life is generally determined by education, experience and exercises they had in their childhood. Mental religious development in adolescence (al-murahiqah) is in line with their physical and spiritual development.